Methods to enhance the functioning of integrated information and telecommunication systems and networks - Юдін, О.К.; Яковенко, О.Л. (Proceedings of National Aviation University (archive), 2008)
Methodology of effectiveness and function increasing of integrated telecommunicational systems and networks was designed on the basis of bi-indication structural coding of date methods for compressing of informational flows.